2007
DOI: 10.2169/internalmedicine.46.0236
|View full text |Cite
|
Sign up to set email alerts
|

Switching from Premixed Human Insulin to Premixed Insulin Lispro: A Prospective Study Comparing the Effects on Glucose Control and Quality of Life

Abstract: Aim

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 11 publications
(3 reference statements)
0
40
0
Order By: Relevance
“…The study populations had a median hemoglobin A1c of 8.7 percent (range: 7.3 to 10.7 percent), a median body mass index of 29.4 kg/m 2 (range: 24 to 37 kg/m 2 ), and a median duration of diabetes of 11 years (range: 4 to 16 years). Eleven trials enrolled insulin-naïve patients (9;18;19;27;29;33;34;36;38;43;44), 26 enrolled insulin-treated patients (23;25;28;32;34;35;37;39-42;45-55;57-60), and nine did not specify history of insulin treatment (17;20-22;24;26;30;31;56). …”
Section: Resultsmentioning
confidence: 99%
“…The study populations had a median hemoglobin A1c of 8.7 percent (range: 7.3 to 10.7 percent), a median body mass index of 29.4 kg/m 2 (range: 24 to 37 kg/m 2 ), and a median duration of diabetes of 11 years (range: 4 to 16 years). Eleven trials enrolled insulin-naïve patients (9;18;19;27;29;33;34;36;38;43;44), 26 enrolled insulin-treated patients (23;25;28;32;34;35;37;39-42;45-55;57-60), and nine did not specify history of insulin treatment (17;20-22;24;26;30;31;56). …”
Section: Resultsmentioning
confidence: 99%
“…56 In the third study, a crossover design study of 28 adolescent subjects, there was no significant difference in HbA1c between subjects treated with glargine/lispro and those treated with NPH/regular insulin, each for 16 weeks (8.7% vs. 9.1%; P=0.13). 55 A number of studies have assessed HbA1c levels in patients treated with premixed human insulins versus those treated with premixed insulin analogs, including premixed insulin lispro formulations [57][58][59] and insulin aspart formulations. [60][61][62] While one study showed small but significant improvements in HbA1c levels after treatment with 50/50 premixed insulin lispro relative to premixed human insulins, 57 other studies failed to find similar advantages favoring premixed insulin analogs.…”
Section: Clinical Effects Of Insulin Analogs Hba1cmentioning
confidence: 99%
“…55 A number of studies have assessed HbA1c levels in patients treated with premixed human insulins versus those treated with premixed insulin analogs, including premixed insulin lispro formulations [57][58][59] and insulin aspart formulations. [60][61][62] While one study showed small but significant improvements in HbA1c levels after treatment with 50/50 premixed insulin lispro relative to premixed human insulins, 57 other studies failed to find similar advantages favoring premixed insulin analogs. 58,60,62 Consistently, however, patients receiving premixed insulin analogs exhibited improved PPG control relative to premixed human insulins, reflecting the higher absorption rate of the analogs.…”
Section: Clinical Effects Of Insulin Analogs Hba1cmentioning
confidence: 99%
“…3 April 2011 JMCP Supplement to Journal of Managed Care Pharmacy S11 aspart 70/30 was less effective than premixed human insulin in reducing fasting glucose (pooled mean difference = 8.3 mg/dL; 95% CI = 0.16 to 16.5 mg/dL; P = 0.04). In 1 of 2 trials on insulin lispro 50/50, 47 no difference in fasting glucose change was observed between the premixed analogue and NPH/regular 70/30. However, in the second trial, 46 insulin lispro 50/50 was less effective than the premixed human insulin preparation (mean difference = 30.0 mg/dL; P < 0.001).…”
Section: Figurementioning
confidence: 95%
“…• Insulin aspart 70/30 versus NPH/regular 70/30-3 parallel-arm trials 31,33,34 and 3 crossover trials [35][36][37] • Insulin lispro 75/25 versus NPH/regular 70/30 or NPH/regular 50/50-9 randomized crossover studies [37][38][39][40][41][42][43][44][45] and 1 retrospective observational study 28 • Insulin lispro 50/50 versus NPH/regular 70/30 or NPH/ regular 50/50-3 randomized crossover studies 38,41,46 and 1 parallel-arm study 47 The studies varied considerably in therapy administration methods, dosing schedules, and duration.…”
Section: Premixed Insulin Analogues Versus Premixed Human Insulinmentioning
confidence: 99%